2015
DOI: 10.1007/s10930-015-9618-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Purification and Characterization of Acetyl Xylane Esterase from Anoxybacillus flavithermus DSM 2641T with Activity on Low Molecular-Weight Acetates

Abstract: Family 4 carbohydrate esterases (CE-4) have deacetylate different forms of acetylated poly/oligosaccharides in nature. This family is recognized with a specific polysaccharide deacetylase domain assigned as NodB homology domain in their secondary structure. Most family 4 carbohydrate esterases have been structurally and biochemically characterized. However, this is the first study about the enzymological function of pdaB-like CE4s from thermophilic bacterium Anoxybacillus flavithermus DSM 2641(T). A. flavither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To determine the esterase activity, zymogram staining was performed with minor modifications as described previously 14 at two different temperatures (+4 C and also at RT) on SDS-PAGE (15%). In brief, followed by electrophoresis the gels were incubated in 100 mM Tris-HCl (pH 7.5) including 0.5% Triton X-100, for 6 h at +4 C and for 4 h at RT.…”
Section: Zymographymentioning
confidence: 99%
“…To determine the esterase activity, zymogram staining was performed with minor modifications as described previously 14 at two different temperatures (+4 C and also at RT) on SDS-PAGE (15%). In brief, followed by electrophoresis the gels were incubated in 100 mM Tris-HCl (pH 7.5) including 0.5% Triton X-100, for 6 h at +4 C and for 4 h at RT.…”
Section: Zymographymentioning
confidence: 99%
“…Malectin [39] and Ricin B lectin domain [40] have carbohydrate recognition function. GH11 is also found associated with other catalytic domains active against different constituents of the plant cell wall, such as the polysaccharide deacetylase domain [41], the esterase domain [42] and the lipase GDSL domain [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ekinci et al [12] reported an 85% yield and 1.3-fold purification of a lipase from G. stearothermophilus AH22 using 70°C. Also, heat treatment was used to purify a lipase from Staphylococcus aureus, and the yield was 74.6%, and the purification fold was 1.57-fold using 55°C [32].…”
Section: Enrichment Of Lipases From Cell Lysatesmentioning
confidence: 99%